Association between Platelet Count and In-Hospital Mortality in Critical Patients with Multiple Myeloma: A Cohort Study - Yan Zeng; Shisong You; Ruili Yuan; Shuhan Yue; Jingwei Zhang (PLoS ONE, 2025)
Background Multiple myeloma (MM) is a malignant blood disease characterized by the abnormal proliferation of immature plasma cells in the bone marrow. Changes in platelet counts (PLT) may significantly impact patient mortality. This study investigates the correlation between platelet counts and mortality rates in critically ill multiple myeloma patients admitted to the Intensive Care Unit (ICU). Methods A retrospective cohort study was conducted with 242 patients diagnosed with MM. Data on platelet count(PLT), red blood cell count(RBC), serum calcium levels, International Normalized Ratio (INR), Sequential Organ Failure Assessment (SOFA) Score, Simplified Acute Physiology Score II (SAPS II), and comorbidities were collected. The study captured the highest and lowest values of laboratory data for patients during their ICU admission. Logistic regression analysis and smooth curve fitting technique were used for analysis. Subgroup analysis was applied to detect cross interactions. Sensitivity analysis was applied to detect consistency. Results When the minimum PLT (PLT-min) were treated as a continuous variable at every 10 × 109/L, the multivariate logistic regression analysis revealed that decreased PLT-min levels was an independent risk factor for mortality rate of critically ill patients with MM [Odds ratio (OR)=0.94, 95% confidence interval (95% CI): 0.89‑0.99, p = 0.023]. Additionally, when PLT-min levels were categorized into tertiles as <95 × 109/L (group 1), 95–160 × 109/L (group 2), and >160 × 109/L (group 3), a decrease in PLT-min levels was also associated with an increasing trend in hospital mortality rate. Compared to group 1, the OR values of group 2 and group 3 were 0.40((95% CI:0.15–1.07, p = 0.069) and 0.30 (95% CI: 0.11‑0.82, p = 0.020). The relationship between PLT-min and in-hospital mortality was found to be nonlinear. Subgroup analysis showed no significant interactions. Similar results were obtained when analyzing the association of maximum PLT(PLT-max) and mortality rate. Conclusions In MM patients in ICU, both minimum and maximum PLT were significantly associated with an increased risk of in-hospital mortality in critical ill patients with MM. These findings are important and warrant further investigation.